2019
DOI: 10.1111/1365-2435.13351
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fungal community composition in decomposing leaf litter and home‐field advantage effects

Abstract: Increasing evidence suggests that specific interactions between microbial decomposers and plant litter, named home‐field advantage (HFA), influence litter breakdown. However, we still have limited understanding of whether HFA relates to specific microbiota, and whether specialized microbes originate from the soil or from the leaf microbiome. Here, we disentangle the roles of soil origin, litter types and the microbial community already present on the leaf litter in determining fungal community composition on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 61 publications
(109 reference statements)
2
76
0
1
Order By: Relevance
“…The hypothesis is that home-field advantage effects are driven by species-specific associations between plants and decomposer communities (Freschet et al, 2012a;Austin et al, 2014). Recent experimental work showed that different litter types can indeed harbor specific litter microbiomes (Keiser et al, 2011;Lin et al, 2019) and that variation in abundant litter fungal groups can contribute to home-field advantage effects (Veen et al, 2019). This results in plant-specific patterns in nutrient release (Perez et al, 2013) and, hence, may contribute to littermediated PSFs.…”
Section: Biotic Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis is that home-field advantage effects are driven by species-specific associations between plants and decomposer communities (Freschet et al, 2012a;Austin et al, 2014). Recent experimental work showed that different litter types can indeed harbor specific litter microbiomes (Keiser et al, 2011;Lin et al, 2019) and that variation in abundant litter fungal groups can contribute to home-field advantage effects (Veen et al, 2019). This results in plant-specific patterns in nutrient release (Perez et al, 2013) and, hence, may contribute to littermediated PSFs.…”
Section: Biotic Pathwaysmentioning
confidence: 99%
“…(3) Elucidate the species-specificity of litter-mediated PSF effects. Evidence is accumulating that plant litters build up unique decomposer communities (Lin et al, 2019;Veen et al, 2019), which may drive litter-mediated PSF via the biotic plant pathway. This may however generate relatively unspecific feedback effects, because different plant species may all profit from nutrients liberated from litter by specialized decomposer communities, however this is not tested.…”
Section: The Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Since soil fungi are saprophytic, diversity may have increased if cover crops were left to decompose [60]. This likely would have result in compositional differences in fungal communities, as decomposers are strongly affected by plant litter type [114].…”
Section: Effect Of Cover Crop Diversity On Fungal Diversitymentioning
confidence: 99%
“…In many "home vs away" studies, plants perform better when grown with soil from the same region as the plant [56][57][58]. Moreover, decomposition rate is increased when a plant litter is sympatric to the soil compared to allopatric soils [59,60]. Since plant-microbe interactions heavily depend on genotypic differences [61] and resource availability [40,62], microbial communities under native plants may differ compared to common cultivar cover crops, leading to differences in ecosystem services and possibly the suppression of pathogens.…”
Section: Introductionmentioning
confidence: 99%